Factors Influencing Attitudes toward Astrology and Making Relationship Decisions Among Thai Adults - Temcharoenkit, Sasiwimon; A. Johnson, Donald (Scholar: Human Sciences, 2021)
This research analysed the impact of astrology on personal relationship decision making in Thailand. There were two objectives: 1) to examine Thai people’s attitudes and behaviour toward fortune tellers, and 2) to examine the impact of fortune telling on decisions about matters of love. Data were collected using an online survey from 253 Thai people. The majority of the sample respondents (58%) were in the 29-39 age range, 50.4 percent were female, and most of the respondents were university graduates (55% with a bachelor’s degree and 32% with a master’s degree). The results indicated that Thai females in the sample have a stronger belief in fortune telling, which held a direct impact on their decision making in their love life. In contrast, Thai males have comparatively less interest in astrology. In consideration of the literature, it was hypothesised that there would be a different impact of fortune telling on single and married people’s decision making about relationship decisions, but no significant difference was found, which suggests that there is an equal impact of astrology on both single and married people. Educational level also did not predict attitude toward nor the use of fortune tellers. Nevertheless, consulting fortune tellers was very popular among this Thai sample. Everyone reported that they consult a fortune teller at least once or twice a year.